GAS CHROMATOGRAPHY TECHNIQUE OPTIMIZATION FOR CHECKING RESIDUAL ETHANOL IN THE PREPARATION OF HETEROLOGOUS ANTI-RABIES IMMUNOGLOBULIN - S. V. Generalov; M. N. Kireyev; E. G. Abramova; O. A. Lobovikova (Acta Biomedica Scientifica, 2012)
The article presents the results of determination of residual ethanol in the preparation of heterologous antirabies immunoglobulin, using portable photoionization gas chromatograph PGC-1. The advantages of the method are as follows: accuracy, sensitivity, promptness. It does not require sample preparation; the results can be processed automatically.